Avaliação imunomolecular e ativação de retrovírus endógenos em pacientes portadores de síndrome mielodisplásica - Vitoriano, Bruna Ferreira (2019)
Myelodysplastic syndrome (MDS) is a group of clonal diseases characterized by hematopoietic progenitor defects and chronic immune dysregulation. The only drugs capable of altering the natural history of MDS are the hypomethylating agents azacitidine and decitabine. An antiviral response activated by hypomethylating agents induces immune responses against malignant cells via endogenous retroviruses (HERV) and interferon pathway regulators (IRFs), and these mechanisms may influence the evolution of MDS. The objective of this study was to evaluate changes in the gene expression of HERVs, IRFs, Toll Receptor-3 (TLR3) and PD1 ligand, PDL1, from the immunological checkpoint in patients with MDS. Bone marrow samples were obtained from 77 MDS patients, six patient samples pre / post treatment with hypomethylating agents and four controls. For the analysis of the gene expression, the real-time polymerase chain reaction (qPCR) technique was performed. There was an increase in the expression of IRF3 in patients with karyotype with aneuploidy (p = 0.020), hemoglobin less than 8 g / dL (p = 0.005), platelets smaller than 50 mm3 (p = 0.011), 2 or 3 cytopenias (p= 0.019) and with transfusion dependence (p = 0.001). The expression of IRF7 in patients with low risk was decreased (p = 0.046). ERV3-1 expression was decreased in patients with altered karyotype with del (5q) (p = 0.038), neutrophils smaller than 800 mm3 (p = 0.005) and increased in dyseritropoiesis (p = 0.016). Patients with hypercellular marrow had increased ERVK6 expression (p = 0.027). There was an increase in the expression of ERVW1 and TLR3 in patients with dyseritropoiesis (p = 0.044). PDL1 was hyperexpressed in patients with normal karyotype (0.003) and one change (p = 0.010) and in patients with two dysplasias (p = 0.005). The IRF3, IRF7, ERVK6, ERV3-1 and TLR3 expression mean were increased after treatment with hypomethylating, but with no significance. There was a strong correlation between the ERVW1 and ERVK6 genes (r = 0.859, p = 0.000), ERVW1 and ERV3-1 (r = 0.801, p = 0.000) and a moderate correlation between the IRF3 and IRF7 genes (r = 0.561 ; p = 0.000) and the ERVK6 and ERV3-1 genes (r = 0.649; p = 0.000). In this study, we found significant genetic and clinical correlations regarding the expression of IRF3, IRF7, ERVK6, ERV3-1, ERW1, TLR3 and PDL-1 genes. We have observed that hypomethylating therapy seems to promote a type I interferon-mediated immune response triggered by HERV expression and recognition by molecules of innate immunity. The presence of erythroid dysplasia in SMD may be due, at least in part, to the activation of HERV, leading to the activation of Toll-like receptors 3, which eventually lead to the activation of IRF-3. Finally, IRF-3 overexpression is associated with great genomic instability with an aneuploid karyotype, severe cytopenias and transfusion dependence, all markers of unfavorable prognosis in this disease with extremely heterogeneous behavior.